Output Torque and Speed Influence by Trapped-oil of Gear Motor and Its Ripple Minimization Strategy - Rui Peng; Jianfeng Wang; Ziwen Sun (Jixie chuandong)
In order to clarify the influence mechanism of trapped-oil on output torque and speed of gear motor and its ripple minimization strategy，from its special trapped-oil characteristics analysis and two aspects of double tooth meshing and single tooth meshing，the proprietary calculation formula between partitions of output torque is established. Then from pressure difference energy of injected medium is equal to power energy of motor output，the proprietary calculation formula between partitions of output speed is established. Finally，according to the special meshing position of maximum and minimum torque，the axial double-pairs structure with minimum ripple is given. The results show that，trapped-oil phenomenon of gear motor is relatively mild，conventional double rectangular relief groove is suitable for relieving trapped-oil pressure. The tooth number is the biggest factor affecting torque and speed ripple，the ripple coefficients of torque and speed under the tooth number of 10 are 0.26 and 0.3，the idling motor gear is advantageous to double-pairs structure to minimize output torque and speed ripple，and following improvement rates are 61.5% and 65.3%，respectively，etc. It is concluded that lightweight through fewer teeth and ultra-low ripple through axis double-pairs with dislocation meshing can be perfectly fulfilled，which provides the basis for the further research and development of high quality gear motor.